Case Study: Review of Islamic Law on the Practice of Buying and Selling Land in Conflict at the Mungkid District Court in Lawsuit of Acts Against the Law - Waluyo Sudarmaji; Muhlil Musolin; Muhajir Muhajir; Abdul Basit (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
It has become commonplace in society there is muamalah buying and selling. The same is true in rural communities. The reflection of the attitude of the people who are still innocent sometimes becomes a problem in the complex problems of life. Among the muamalah that often become legal problems are cases of buying and selling land because the practice of buying and selling is carried out by the community only based on mutual trust without being supported by the correct administrative process. This study intends to describe the practice of buying and selling land that started from a buying and selling of mutual trust which later became a dispute over a lawsuit filed against the law in the Mungkid District Court in the perspective of Islamic law. The research method is qualitative paradigm research with a case study approach. The location of this research is in Demangan Hamlet, Kebonrejo Village, Salaman District, Magelang Regency. Sources of data were obtained using participatory observation, interviews, and documentation. After being analyzed, the researcher concluded that there had been four transactions in one land object which was broken up, of which three transactions were legal according to Islamic law, while the fourth transaction was invalid because it included buying and selling gharar.